"Poking around and reading the tea leaves": analysis of issues affecting film and TV unions. Issue 1 (3rd August 2020) - Fuller, Ryan P.; Michael, Boniface
Abstract : Purpose: This research investigates the issues of concern for American film and television (TV) unions, the features of issues, whether issues are threats, opportunities or mixed evaluations, and unions' distributive or integrative approaches to issues (Walton and McKersie, 1965). Design/methodology/approach: The first author interviewed 25 union leaders and used thematic analysis to identify issue characteristics and evaluations of issues as threats, opportunities or mixed. Using language analysis, the authors then connected these evaluations to integrative or distributive approaches. Findings: The findings revealed three larger issues of concern (positioning the union and jurisdiction, shifting patterns of risk and negotiating and enforcing contracts) and five characteristics (locus, boundary, manageability, predictability and scope). These characteristics then determined how interviewees viewed issues as threats, opportunities or mixed evaluations. Three characteristics grouped together to form threats: external locus, indistinct boundaries and low manageability. Indistinct boundaries contributed to assessments of issues as mixed. These issue types, characteristics and interpretations revealed a metaphorical above- and below-the-line differentiation among film and TV unions based on the members continued ownership of their work. With one exception – BTL unions on positioning union and jurisdiction – leaders' language reflected distributive approaches to issues. Originality/value: This study delves deeper into Walton and McKersie's (1965) classical two-part classification of issues by adding a typology of characteristics and operational definitions to aid in identifying threats, opportunities and mixed evaluations through the novel use of issue analysis in industrial relations.